Editorial - Diaz Dumont, Jorge Rafael (2023)
The National Autonomous University of Tayacaja Daniel Hernández Morillo, presents Vol. 4, No 1 (2023) of the Journal of Scientific and Technological Research "Llamkasun" which is a publication published every six months by the UNAT and managed through the Open Journal System. Its objective is to publish articles that are the results of concluded investigations that preserve a character of originality, utility, scientific and technological relevance; that contribute new knowledge on theoretical or practical aspects in the specialty of "Civil Engineering, Industrial Processes and Technologies", according to the indicated norms. Certified Magazine with ISO 9001:2015 - Certificate PE22/819943899 (Publication of scientific articles with implemented processes of the quality management system - SGS). The Llamkasun Scientific and Technological Research Journal certifies the quality in the publication of original scientific articles, reviewed by expert blind peers and with a very strict similarity system that guarantees the originality of each article for publication. Additionally, the layout and design process of each scientific article was also certified.